2009
DOI: 10.1159/000204901
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18 Fluorodeoxyglucose with Positron Emission Tomography Revealed Bone Marrow Involvement in Sarcoidosis Patients with Anaemia

Abstract: sion: Whole-body 18 F-FDG PET imaging should be considered in sarcoidosis patients with symptomatic anaemia. It can noninvasively suggest bone marrow involvement, indicate sarcoidosis treatment and monitor its efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…As PET-CT is not routinely used for the diagnosis of sarcoidosis, there is no correct data about BM involvement rates yet. Yanardag and de Prost reported that, BM involvement must be suspected in case of anemia in a sarcoidosis patient [20,21]. In our study, BM involvement determined by PET-CT was significantly different between the two groups favoring the patients with lymphoma (p < 0.001).…”
Section: Discussioncontrasting
confidence: 38%
“…As PET-CT is not routinely used for the diagnosis of sarcoidosis, there is no correct data about BM involvement rates yet. Yanardag and de Prost reported that, BM involvement must be suspected in case of anemia in a sarcoidosis patient [20,21]. In our study, BM involvement determined by PET-CT was significantly different between the two groups favoring the patients with lymphoma (p < 0.001).…”
Section: Discussioncontrasting
confidence: 38%
“…This suggests that age-related changes in females, such as the hormonal dysregulation associated with menopause, may contribute to sarcoidosis. Although significant heterogeneity in disease presentation and disease severity occurs among different ethnic and racial groups [13,14,15,16], both of these pulmonary granulomatous diseases, sarcoidosis and nontuberculous mycobacterial disease, are likely to be characterized by a preponderance in postmenopausal females. Therefore, it is likely that fluctuations of sex hormones may be associated with enhanced granuloma formation in the lung.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchiectasis is uncommon form of sarcoidosis [21]. Anaemia is uncommon but if present, it is usually anaemia of chronic disease or autoimmune haemolyticanaemia can occur [22]. There can be leukopenia, eosinophilia.…”
Section: Discussionmentioning
confidence: 99%